Secular Variability of the Upwelling at the Canaries Latitude: An Instrumental Approach - Gallego, D.; García Herrera, Ricardo Francisco; Mohino Harris, Elsa; Losada Doval, Teresa; Rodríguez De Fonseca, María Belén (Journal of Geophysical Research: Oceans, 2022)
We thank Dr. Clive Wilkinson for his assistance with the UK National Archives collection. Esther González did intensive work abstracting logbooks. Research funded by the Spanish Ministerio de Economía y Competitividad under grant CGL2015-72164-EXP (UPNAO). E.M., T.L. and B.R. also thank the support of EU-TRIATLAS project (grant agreement 817578). Funding for open access publishing: Universidad Pablo de Olavide/CBUA. In this research we make use of historical wind direction observations to assemble an instrumental upwelling intensity index (the so-called Directional Upwelling Index [DUI]) for the coast of Northwest Africa between 26 degrees and 33 degrees N and from 1825 to 2014. The DUI is defined as the persistence of the alongshore winds at the coast and unlike other upwelling indices, it relies on observed wind direction solely, avoiding the suspected bias toward increasing wind speed of historical wind observations documented in previous research. We have found that between June and October, when the upwelling intensity in the area is at its seasonal maximum, the persistence of the north-easterlies measured by the DUI is significantly related to the alongshore wind stress and subsequently with Sea Surface Temperature anomalies at the coast of NW Africa. The analysis of the DUI record does not display a consistent long-term trend but an oscillatory behavior. At interannual time scales this variability can be linked to the changes in the strength and location of the subtropical north Atlantic high-pressure center and at multidecadal scales, the upwelling seems mainly driven by the Atlantic Multidecadal Variability through the modulation exerted by this climatic pattern on the intensity of the Saharan low. Unión Europea. Horizonte 2020 Ministerio de Economía y Competitividad (MINECO) Depto. de Estructura de la Materia, Física Térmica y Electrónica Fac. de Ciencias Físicas TRUE pub